Ontogeny of Intestinal Glucose Transport in Heavy and Light Body Weight Turkey Poults1 - Suvarna, S.; Christensen, V.L.; Ort, D.T.; Croom, W.J. (International Journal of Poultry Science, 2004)
Development of intestinal tissue was measured in newly hatched poults. Both anatomical and physiological measurements were made on poults produced by two half sibling sires with hens that were their full or half siblings. The poults from one sire (HBW) weighed more at hatching than those from the other sire (LBW). Survival of the heavier poults was poor indicating metabolic insufficiencies. A significant positive correlation was noted between hatchling body weights and blood glucose concentration (Christensen et al., 2000a), and this was accompanied by depressed gluconeogenesis in HBW poults. The hypothesis was proposed that the HBW poults with elevated plasma glucose concentrations might have greater glucose absorption from intestinal tissue than did the LBW poults. The data confirmed heavier weights in HBW poults than LBW, and HBW jejunum weight relative to body weight was less than that of LBW. The poults did not differ in intestinal length, glucose transport, maltase activities or plasma triiodothyronine and thyroxine or glucose concentrations. The HBW poults also utilized less yolk during development than did the LBW indicating that the HBW embryos rely more on gluconeogenesis for survival during development than do the LBW. It was concluded that the increased body weight of HBW poults compared to LBW may be due to increased absorption of all nutrients because of a greater intestinal mass relative to body weight rather than to differences in glucose digestion and uptake rates.